1995
DOI: 10.1155/s1064744995000391
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Ability of the Group B Streptococci to Inhibit Gram‐Positive and Gram‐Variable Constituents of theBacterial Flora of the Female Genital Tract

Abstract: Objective: The purpose of this study was to analyze the ability of septicemic and nonsepticemic isolates of group B streptococci (GBS) to inhibit in vitro the principal bacterial groups found in the normal bacterial flora of the female genital tract.Methods: The target groups were composed of 1) 10 strains each of the following: viridans streptococci, nonhemolytic streptococci (not group B or D), group A streptococci, GBS, peptostreptococci, coagulase-negative staphylococci, Staphylococcus aureus, and Gardnere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 18 publications
0
22
0
Order By: Relevance
“…Multiple studies have found that S. agalactiae inhibits Lactobacillus spp. and G. vaginalis without inhibiting S. aureus (34)(35)(36) and that S. aureus colonization is significantly associated with colonization by S. agalactiae in a population of pregnant women (37). Our findings thus illustrate another way in which GBS could promote the virulence of S. aureus.…”
Section: Discussionmentioning
confidence: 54%
“…Multiple studies have found that S. agalactiae inhibits Lactobacillus spp. and G. vaginalis without inhibiting S. aureus (34)(35)(36) and that S. aureus colonization is significantly associated with colonization by S. agalactiae in a population of pregnant women (37). Our findings thus illustrate another way in which GBS could promote the virulence of S. aureus.…”
Section: Discussionmentioning
confidence: 54%
“…The more severe the microscopic findings, the more likely these organisms will be cultured. Case studies have recently drawn attention to the possibility of vaginitis due to group B streptococci 4 , and Monif et al provide in vitro evidence that group B streptococci inhibits growth of lactobacilli and G. vaginalis, but not S. aureus 22,23 . There is increasing evidence that some pregnant women develop mid-trimester chorioamnionitis caused by invasive group B streptococci 24,25 .…”
Section: Vaginal Fluid Constituents No Infection Candida Vaginitis Bamentioning
confidence: 99%
“…3 The GBS strains tested did not inhibit the growth of coagulase-negative staphylococci, S. aureus, or any gram-negative organisms. 3 Isolates of GBS were uniformly inhibited by coagulase-negative staphylococci, but were not inhibited by S. aureus. 4 When quantitative studies were performed analyzing the interrelationships within the bacterial flora of the female genital tract, GBS was found not to be an infrequent isolate with either G. vaginalis, lactobacillus, or the coagulasenegative staphylococci.…”
Section: Discussionmentioning
confidence: 89%
“…3 In vitro, GBS was shown to inhibit other beta hemolytic streptococci, diphtheroides, lactobacillus, and Gardnerella vaginalis. Variable inhibition by GBS was observed with viridans, streptococci, nonhemolytic (not group B or D) streptococci, peptostreptococci, and enterococci.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation